INSTANTANEOUS PRODUCTION GROWTH IN A DYNAMIC ECONOMY - Villalobos Céspedes, Daniel (2023)
The purpose of this study is to measure the average and instantaneous rates of production growth and to provide new formulas for measuring the contribution to and share of resources in that growth. This is the key idea in a new method of attack as suggested by Cobb and Douglas—as of yet not solved by economic growth theory—to demonstrate that distribution processes are modeled on those of the production of value. We intend to validate the strength of the proposed model by systematizing and analyzing production, investment and employment data from a dynamic economy, i.e., the United States of America, provided by the Bureau of Economic Analysis (BEA) and the Federal Reserve (Fed) for the years 2012 to 2022, the results of which can be found in the Appendix. We conclude that greater convergence with equity between labor and capital contribution and share in production growth results when the elasticity of its composition  is between ½ and 1. Outside of this range, we see divergence with inequity adverse to labor. Our model could improve the formulation and execution of macroeconomic policies (fiscal, monetary and trade) and promote greater convergence/equity in the contribution to and share of resources in production growth.